Adult attachment and dehumanization among Chinese college students: trait attachment and state attachment perspectives - Guo, Minna; Xu, Beibei; Wang, Haiyao; Le, Thi Quynh Mai; Yan, Zhihao; Sang, Qingsong (Frontiers in Psychology, 2024)
Introduction Current social issues such as bullying, online violence, and local conflicts are all prominent topics in the field of psychology and linked to dehumanization. However, research on dehumanization from a non-Western background has been rare. As a key factor influencing individual behavior, attachment has not been sufficiently integrated into studies on dehumanization. Therefore, this study provides empirical evidence to explore the relationship between adult attachment (both trait and state) and dehumanization. The sample consisted of college students from China. Methods In Study 1 (N = 705) latent profile analysis was employed to exploring the potential categories of trait adult attachment in China, and to investigate how these categories impact dehumanization. Study 2 (N = 281) focused on activating secure attachment and examined the effects of three state attachment types, security, avoidance and anxiety, on dehumanization. Results Study 1 identified four types of adult attachment: preoccupied, secure, fearful, and dismissing, and revealed that these different attachment types have varying impacts on dehumanization. Study 2 showed that both security and avoidance predict dehumanization. Discussion This research established a link between adult attachment and dehumanization, offering new insights into the psychological mechanisms underlying dehumanization and suggesting novel strategies for its prevention and intervention.